Sustainability and CSR orientation through "Edutainment" in tourism - Mara Del Baldo (International Journal of Corporate Social Responsibility (JCSR), 2018)
The aim of the paper is to present and discuss, using a fieldwork approach, the pillars and the outcomes of sustainable business models in the tourism sector. After having traced the theoretical framework, which combines the literature strands of sustainable tourism and sustainable business model, the work is centered on the analysis of an exemplary case-study. On the basis of an action-research approach, it focuses on the experience of Costa Edutainment Spa, Italian leader in the management of public and private structures dedicated to recreational, cultural and educational activities. Findings show that that the CSR and sustainability orientation which affects the business model lies on both the culture and the identity of the company which is characterized since its foundation by a deep socio-economic involvement. Promoted by the entrepreneurial family. Moreover, the set of key values (responsibility towards people, the environment and the society) and external factors affecting the cultural and touristic sector the company belongs to, favour the development of educational projects addressed to stakeholders (customers, suppliers, scientific community, research centres) aimed at building up innovative paths of sustainability.
Keywords: 650; CSR; Sustainable business model; Strong sustainability; Education; Entertainment; Tourism